To your eternity. 17 - Ōima, Yoshitoki (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2022)
"It is evident that Fushi's old comrades struggle to adjust to their modern surroundings. His friends express interest in leaving their shared home, and Fushi begins to feel a devastating new emotion. Mizuha, however, has something more sinister in store for him"--